Performance analysis and optimization of a five-degrees-of-freedom compliant hybrid parallel micromanipulator. (August 2015) - Zhang, Dan; Gao, Zhen
Abstract: There are generally two main directions for the investigation and development of parallel manipulators, namely macro/meso stream and micro/nano stream, in which the former one has been thoroughly investigated in recent decades, while the latter one still remains many performance related open issues that significantly affect their application potentials in critical situations such as high-precision automated cell manipulation. Improving the overall performance of parallel manipulators is the bridge to connect the academia and industry for the great development and real-world application. This research is to develop a novel methodology called performance decomposition and integration for governing the design optimization process of complicated micromanipulator. A new five degrees-of-freedom (DOF) compliant hybrid parallel micromanipulator which is configured with five identical PSS limbs and one constraining UPU limb is proposed as a case study. The performance visualization, finite element analysis, and dimensional optimization are implemented. The proposed methodology is applicable for the design improvement of different kinds of compliant/parallel mechanisms. Highlights: Performance is a critical topic for the further improvement of compliant parallel mechanisms. The research attempts to propose a paradigm called performance decomposition and integration to manage the overall performance of these mechanisms in a higher level. A CHPMM is proposed as an example to showcase part of the principle of PDI in the process of design and optimization. The proposed method can be well integrated with the methodology of system hybridization through the specific methods of mechanism hybridization, actuation hybridization and optimization hybridization. For the future work, a physical prototype will be manufactured to further improve the overall performance in aspects of manipulation and control under the guidance of the proposed methods.